2021
DOI: 10.1111/jvim.16052
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with clinical interpretation of tracheal wash fluid from dogs with respiratory disease: 281 cases (2012‐2017)

Abstract: Background: Clinicians face several dilemmas regarding tracheal washes (TWs) for the diagnosis of respiratory disease, including method and prediction of bacterial growth from cytology results. Objective: To compare cytology and culture of endotracheal and transtracheal washes and identify factors associated with discordancy and bacterial growth. Animals: Two hundred forty-five dogs with respiratory disease. Methods: Retrospective study. Tracheal wash submissions were included if cellularity was sufficient for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A recent study examining TW cytology results from dogs with respiratory disease revealed similar results of discordancy with a high number of cytology negative and culture positive results (55.4%). 33 Pre-treatment with antibiotics may affect cytology results and as no information was provided on the administration of medication to patients before sample collection in our study, this influential factor cannot be excluded. 2,33 In addition, culture of commensal organisms in animals with noninfectious respiratory disease may have also affected these results or even bacteria that are difficult to culture but still detectable on cytology.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A recent study examining TW cytology results from dogs with respiratory disease revealed similar results of discordancy with a high number of cytology negative and culture positive results (55.4%). 33 Pre-treatment with antibiotics may affect cytology results and as no information was provided on the administration of medication to patients before sample collection in our study, this influential factor cannot be excluded. 2,33 In addition, culture of commensal organisms in animals with noninfectious respiratory disease may have also affected these results or even bacteria that are difficult to culture but still detectable on cytology.…”
Section: Discussionmentioning
confidence: 88%
“…33 Pre-treatment with antibiotics may affect cytology results and as no information was provided on the administration of medication to patients before sample collection in our study, this influential factor cannot be excluded. 2,33 In addition, culture of commensal organisms in animals with noninfectious respiratory disease may have also affected these results or even bacteria that are difficult to culture but still detectable on cytology. One example of this is Mycoplasma spp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The trachea and main stem bronchi constitute a central site of exposure to all inhaled materials and central airway sampling from these sites could enhance the confirmation of airway inflammation (Zhu et al 2015;Graham et al 2021). Tracheal wash aspiration is the minimally invasive procedure which predominantly samples the larger airways along with a certain amount of sample from the lower airways and the alveoli, for cytologic and culture analysis.…”
Section: Diagnosismentioning
confidence: 99%
“…Tracheal wash aspiration is the minimally invasive procedure which predominantly samples the larger airways along with a certain amount of sample from the lower airways and the alveoli, for cytologic and culture analysis. Contributing factors for better sample extraction includes mucociliary clearance and cough reflex (Cohn and Reinero, 2007;Finke, 2013;Graham et al 2021). Cytological interpretation should include estimated cellularity, differential cell counts and morphologic description of the cells encountered (Creevy, 2009).…”
Section: Diagnosismentioning
confidence: 99%